Farmer Exchange Rate and its Implications for Welfare and Poverty Alleviation in Rural Sulawesi - Yulia Akib, Fitri Hadi; Canon, Syarwani; Baruwadi, Mahludin H.; Saleh, Sri Endang; Hippy, Mohammad Zubair (Journal of International Conference Proceedings, 2025)
This study investigates the relationship between Farmer’s Terms of Trade (NTP) and rural poverty across Sulawesi during the period 2019–2024, aiming to explore how sectoral NTP variations impact farmer welfare and poverty alleviation. Utilizing a quantitative correlational design, this research applies panel data regression on NTP indicators from five agricultural subsectors food crops, horticulture, plantations, livestock, and fisheries spanning six provinces over five years. The regression model demonstrates that these subsectoral NTPs collectively account for 47.55% of the variation in rural poverty. Plantation NTP exhibits a strong and significant negative association with poverty, indicating its efficacy in reducing rural deprivation. Similarly, food and horticulture NTPs also show negative and significant effects. However, contrary to expectations, livestock and fisheries NTPs are positively and significantly associated with poverty levels, suggesting sectoral inefficiencies or market barriers that hinder inclusive welfare outcomes. These findings reveal the complex dynamics of agricultural price mechanisms and their implications for poverty alleviation, underscoring the need for targeted, subsector-specific policy interventions. Strengthening rural infrastructure, stabilizing agricultural markets, and enhancing access to technology and social protection are crucial strategies for transforming farmer exchange conditions into sustained poverty reduction in Sulawesi.